Numerical Simulation of Aircraft Icing Based on the Szilder Random-Walk model - Li, Yu; Chen, Weijian; Yu, Xiaoxiao; Shen, Hao (IET Conference Proceedings, 2018)
Due to the fact that the traditional Messinger model cannot capture the microscopic characteristics of the ice surface well, in this paper, a random-icing model based on the behavior of individual fluid elements is established to simulate the shape and structural details of aircraft ice accretions. The random-icing model includes the ballistic part and the random-walk part. The relevant programs are written by this method, and the icing simulations on NACA 0012 airfoil under different conditions are also carried out. Finally, we compare the simulated ice shapes with the experimental values and the calculation results of CIRAMIL software based on the Messinger model. Although there are some discrepancies between experimental and predicted accretion shapes, the overall agreement is good. In particular, the ice shapes obtained by the random-icing model are rougher and their structural details are more obvious. Therefore, the random-icing model has advantages in predicting the aerodynamic characteristics of icing airfoils.